2020
DOI: 10.1371/journal.pone.0240486
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of Pseudomonas stutzeri W228 for removal of copper and lead from marine environments

Abstract: High concentrations of metals in the environment alter bacterial diversity, selecting resistant and tolerant species. The study evaluated the selection of a potential bacterial strain from Sepetiba Bay-Rio de Janeiro, Brazil marine sediments to remove Cu and Pb. The bacterial strain isolated from the sediments was used in three different bioassays: (1) Cu at concentrations of 0 (control), 6 and 50 μg.mL -1 ; (2) Pb at concentrations of 0 (control), 6 and 50 μg.mL -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This aligns with the results of Coelho da Costa Waite et al who also reported a maximum temperature of 37 °C for P. stutzeri growth in a study on Cu and Pb removal. 63 The percentage of Ni removal increased from 18 to 43.6% with an increase in temperature from 25 to 37 °C by employing free cells. PRHB showed a 47.82% Ni removal capacity at 25 °C, which increased to 67.52% at 37 °C.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This aligns with the results of Coelho da Costa Waite et al who also reported a maximum temperature of 37 °C for P. stutzeri growth in a study on Cu and Pb removal. 63 The percentage of Ni removal increased from 18 to 43.6% with an increase in temperature from 25 to 37 °C by employing free cells. PRHB showed a 47.82% Ni removal capacity at 25 °C, which increased to 67.52% at 37 °C.…”
Section: Resultsmentioning
confidence: 94%
“…This metal ion-resistant bacterium demonstrated resistance to mercury and chromium in our preliminary microbial tolerance study, suggesting its potential for removing these metal ions. Furthermore, studies by Coelho da Costa Waite et al employed P. stutzeri strain W228 to target Cu and Pb removal, 63 while Sathish Kumar et al utilized P. stutzeri L1, 67 and Kumari et al employed P. stutzeri Cr8 for chromium removal. 68 The immobilization of cells on PRHB resulted in a substantial improvement in the removal of both Cd and Ni.…”
Section: Effect Of Temperature Metal Ion Removal Is An Energy-depende...mentioning
confidence: 99%
“…stutzeri LBR and C . metallidurans LBJ are characterized by a high efficiency of lead biosorption compared to the work of Waite and colleagues [ 29 ], who proved that the strain P . stutzeri W228 presents significant results for the absorption of Pb going to concentrations up to 54.0 mg/kg.…”
Section: Discussionmentioning
confidence: 97%
“…The P. stutzeri LBR strain is used in bioremediation technology in environments affected by heavy metals. It is considered cosmopolitan and it presents a range of biochemical and physiological traits such as nitrogen fixation, denitrification and metal biosorption [19,20]. Moreover, P. stutzeri LBR contributes to the degradation of pollutants and interacts with toxic metals [21].…”
Section: Introductionmentioning
confidence: 99%
“…Sommer et al [28] recorded that Pseudomonas stutzeri has a similar physiology in terms of growth rate and nutritional requirements to E. coli and thus has a comparable success rate in being a production host for membrane proteins. In addition, these bacteria also known to be able to bioabsorb Pb [29], improve shrimp farming water quality by converting ammonia and nitrite to nitrate [30], produce protease [31] and amylase [32], bio-adsorption of direct red 80 dye from the Jumputan fabric industry [33], and produce auxin phytohormones [34].…”
Section: Discussionmentioning
confidence: 99%